CTNI-49. PHASE 1 STUDY OF ST101, A FIRST-IN-CLASS PEPTIDE ANTAGONIST OF CCAAT/ENHANCER-BINDING PROTEIN ß, IN PATIENTS WITH ADVANCED SOLID TUMORS, WITH A PHASE 2 EXPANSION IN RECURRENT GLIOBLASTOMA MULTIFORME. (12th November 2021) - Symeonides, Stefan; Evans, Jeff; Arkenau, Hendrik-Tobias; McKean, Meredith; Lakhani, Nehal; Lim, Emerson; Falchook, Gerald; Rotolo, Jim; Capiaux, Gina; Michel, Rob; Kaesshaefer, Stephen; Bexon, Alice
Abstract: BACKGROUND: C/EBPβ is a transcription factor that is active during embryofetal development but held in an inactive state in most mature cells (Zahnow 2009). C/EBPβ is upregulated or overactivated in multiple cancers, where it inversely correlates with disease prognosis and survival due to activation of a gene signature that promotes tumor cell proliferation and survival. ST101 is a cell-penetrating peptide antagonist of C/EBPβ. ST101 exposure leads to selective tumor cell death in multiple human cancer cell lines, including GBM, without impacting normal cell viability. In vivo, ST101 displays rapid uptake into multiple organs, the ability to cross the blood-brain barrier, and a long plasma half-life due to its resistance to degradations. It has potent anti-tumor activity in multiple GBM models, as a single agent or in combination, which supported moving into clinical development. TRIAL DESIGN: This phase 1-2 study is enrolling patients ≥ 18 years of age with advanced, unresectable metastatic solid tumors refractory to or intolerant of other therapeutic options. We began recruitment in August 2020. The primary objective of phase 1 is to evaluate safety and tolerability of ST101. Secondary objectives include the recommendation of a dose and regimen of ST101 for further evaluation, pharmacokinetics, several pharmacodynamic measures, and preliminary efficacy. Patients receive intravenous ST101 once weekly in a standard 3 + 3 design. Enrollment is ongoing, and by 21 May 2021, 15 patients have been recruited in four dose-escalation cohorts up to 4 mg/kg; a 5 th cohort (6 mg/kg) is ongoing. The recommended phase 2 dose will be used in a 15-30 patient GBM expansion cohort, with a Simon 2-stage design, which requires one response or two patients with PFS6 in the first cohort to continue the study. Up to 120 patients are planned in a total of four expansion cohorts, which should be enrolling by Q3 2021.